Association of Short-term Complications With Procedures Through Separate Incisions During Total Ankle Replacement. (October 2016) - Criswell, Braden; Hunt, Kenneth; Kim, Todd; Chou, Loretta; Haskell, Andrew
Background: Surgeons disagree about the safety of adding adjuvant procedures requiring separate incisions during total ankle replacement (TAR). This study tested the hypothesis that complication rates for patients in the first year after TAR would be greater when combined with procedures through separate incisions. Methods: A retrospective review was performed on a consecutive series of 124 patients who underwent total ankle replacement between 2007 and 2013. Demographics, case-specific data, and postoperative complications over the first year were collected. A chi-square analysis was performed to compare differences in complication rates among patients with and without additional procedures requiring a separate incision. The average patient age was 67±10 years. Fourteen patients (11%) were diabetic and 2 patients (2%) were current smokers. Eighty-seven (70%) had prior trauma leading to arthritis. Ninety-seven (78%) cases used the Scandinavian Total Ankle Replacement (STAR), 16 (13%) Salto Talaris, and 11 (9%) In Bone implants. Ten (8%) cases were revisions. Excluding percutaneous Achilles lengthening, 35 of 124 patients (28%) had a total of 54 adjuvant procedures requiring a separate incision during TAR. These included 9 (7%) calcaneal osteotomies, 8 (6%) medial malleolar fixation, 6 (5%) subtalar fusions, 5 (4%) lateral ligament repair, 4 (3%) open Achilles lengthening, 4 (3%) removal of hardware, 2 (2%) first metatarsal osteotomy, and 8 other procedures. Results: Overall, 32 (26%) of the 124 patients had a complication, including 15 (12%) delayed wound healing, 6 (5%) malleolar fracture, and 11 other complications. At 1 year, 24 (27%) of 89 patients without additional incisions and 8 (23%) of 35 patients with additional incisions, excluding percutaneous Achilles lengthening, had any complication ( P = .64). Discussion: This study did not demonstrate an association between additional procedures requiring a separate incision during TAR and early complications. Overall complication rates were similar to previously reported series of TAR. This study suggests that surgeons can add adjuvant procedures during TAR to improve alignment, stability, or treat adjacent segment arthritis without affecting short-term complication rates. The necessity or utility of these adjuvant procedures requires further study. Level of Evidence: Level III, comparative series.